Constraints on formation and evolution of the lunar crust from feldspathic granulitic breccias NWA 3163 and 4881. (15th August 2016) - McLeod, Claire L.; Brandon, Alan D.; Fernandes, Vera A.; Peslier, Anne H.; Fritz, Jörg; Lapen, Thomas; Shafer, John T.; Butcher, Alan R.; Irving, Anthony J.
Abstract: Lunar granulitic meteorites provide new constraints on the composition and evolution of the lunar crust as they are potentially derived from outside the Apollo and Luna landing sites. Northwest Africa (NWA) 3163, the focus of this study, and its paired stones NWA 4881 and NWA 4483, are shocked granulitic noritic anorthosites. They are petrographically and compositionally distinct from the Apollo granulites and noritic anorthosites. Northwest Africa 3163 is REE-depleted by an order of magnitude compared to Apollo granulites and is one of the most trace element depleted lunar samples studied to date. New in-situ mineral compositional data and Rb–Sr, Ar–Ar isotopic systematics are used to evaluate the petrogenetic history of NWA 3163 (and its paired stones) within the context of early lunar evolution and the bulk composition of the lunar highlands crust. The NWA 3163 protolith was the likely product of reworked lunar crust with a previous history of heavy REE depletion. The bulk feldspathic and pyroxene-rich fragments have 87 Sr/ 86 Sr that are indistinguishable and average 0.699282 ± 0.000007 (2σ). A calculated source model Sr TRD age of 4.340 ± 0.057 Ga is consistent with (1) the recently determined young FAS (Ferroan Anorthosite) age of 4.360 ± 0.003 Ga for FAS 60025, (2) 142 Nd model ages for the closure of the Sm–Nd system for the mantle source reservoirs of the Apollo mare basalts (4.355–4.314 Ga) and (3) a prominent age peak in the Apollo lunar zircon record ( c . 4.345 Ga). These ages are ∼100 Myr younger than predicted timescales for complete LMO crystallization (∼10 Myrs after Moon formation, Elkins-Tanton et al., 2011). This supports a later, major event during lunar evolution associated with crustal reworking due to magma ocean cumulate overturn, serial magmatism, or a large impact event leading to localized or global crustal melting and/or exhumation. The Ar–Ar isotopic systematics on aliquots of paired stone NWA 4881 are consistent with an impact event at ⩾ 3.5 Ga. This is inferred to record the event that induced granularization of NWA 3163 (and paired rocks). A later event is also recorded at ∼2 Ga by Ar–Ar isotopes is consistent with an increase in the number of impacts on the lunar surface at this time (Fernandes et al., 2013). Northwest Africa 3163 and its paired stones therefore record a c . 2.4 Gyr record of lunar crustal production, metamorphism, brecciation, impacts and eventual ejection from the lunar surface.